2018
DOI: 10.1021/acs.inorgchem.8b00340
|View full text |Cite
|
Sign up to set email alerts
|

Metal Atom Clusters as Building Blocks for Multifunctional Proton-Conducting Materials: Theoretical and Experimental Characterization

Abstract: The search for new multifunctional materials displaying proton-conducting properties is of paramount necessity for the development of electrochromic devices and supercapacitors as well as for energy conversion and storage. In the present study, proton conductivity is reported for the first time in three molybdenum cluster-based materials: (H)[MoBrS(OH)]-12HO and (H)[MoX(OH)]-12HO (X = Cl, Br). We show that the self-assembling of the luminescent [MoL(OH)] cluster units leads to both luminescence and proton cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Its photoelectrical property stabilization is valid for the development of an optical sensing device. Many reasonable hypotheses have discussed the origin of the redox, photophysical, and photochemical properties of the Mo 6 cluster based on the molecular structure, chemical compositions, and their intrinsic interactions. ,,, Moreover, the proton-conducting properties of the (H) 2 [Mo 6 X 8 (OH) 6 ]·12H 2 O (X = Cl, Br) have been clarified through the hydrogen-bond network that develops between apical hydroxyl groups and the adsorbed water molecules . Kuttipillai et al also suggested that the counter cations can play an important role in charge injection, transport, recombination, and exciton formation in the electrically pumped devices fabricated from the core cluster .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Its photoelectrical property stabilization is valid for the development of an optical sensing device. Many reasonable hypotheses have discussed the origin of the redox, photophysical, and photochemical properties of the Mo 6 cluster based on the molecular structure, chemical compositions, and their intrinsic interactions. ,,, Moreover, the proton-conducting properties of the (H) 2 [Mo 6 X 8 (OH) 6 ]·12H 2 O (X = Cl, Br) have been clarified through the hydrogen-bond network that develops between apical hydroxyl groups and the adsorbed water molecules . Kuttipillai et al also suggested that the counter cations can play an important role in charge injection, transport, recombination, and exciton formation in the electrically pumped devices fabricated from the core cluster .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For blank PLGA nanoparticles, colloidal stability was conserved during the 3 months study whatever the temperature (Supplementary material 1). Figure 3 shows (Daigre et al, 2018;Kirakci et al, 2016Kirakci et al, , 2019Svezhentseva et al, 2017). Encapsulating the cluster in a matrix such as SiO 2 nanoparticles (Aubert et al, 2013), polystyrene microparticles (Efremova et al, 2014) or nanoassemblies with betacyclodextrins (Kirakci et al, 2014) was shown to be a solution to circumvent the tendency to easily hydrolyse in water.…”
Section: Cnps Physico-chemical Stabilitymentioning
confidence: 97%
“…As molybdenum (and tungsten) is sufficiently cheap and abundant, their compounds constitute viable alternatives to costly noble metal-based luminophores, not to mention the environmentally hazardous lead-based hybrid perovskites and cadmium containing quantum dots [ 6 , 7 , 8 ]. Octahedral halide-bridged cluster compounds of Mo(II) and W(II), of the general type [M 6 X i 8 L a 6 ] (M = Mo, W; X i = Cl, Br, I (bridging or “inner”); L a = organic/inorganic ligand (terminal or “apical”, see Figure 1 ) show remarkable photoluminescence properties and emit red light in high quantum yields, which makes them particularly attractive in the design of functional hybrid nanomaterials [ 9 ] with potential applications in optoelectronic [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], lighting [ 19 ], hydrogen storage [ 20 ], biomedicine [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], catalysis [ 30 , 31 ], and photocatalysis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%